A critical discourse analysis of the voices of people with intellectual and developmental disabilities within Australian community access service policies and practice: my voice, my policy. Issue 2 (3rd July 2017) - Evans, Ted; Bellon, Michelle; Matthews, Brian
ABSTRACT: Community access services are designed for people with disabilities to gain and use their abilities to enjoy their full potential for social independence. This research explored the extent to which the voices of people with intellectual and developmental disabilities and their families and informal primary carers have contributed to Australian community access services policy in the twenty-first century. The research aimed to explore whether the voices of people with intellectual and developmental disabilities and their families are present in Australian community access services policy; if community access services policies influence practice with regard to community participation and community inclusion; and what can be learnt from community access services policy and practice across Australia. A critical discourse analysis of Australian publicly available community access services extant texts, published between 2000 and 2014, was performed. The written evidence ( n = 42) included strategic and operational policies and discussion papers. The voices of people with intellectual and developmental disabilities and their families or informal primary carers were evident in 16 out of the 42 documents included in the study. Three key themes emerged that illustrate how policy and practice influenced community participation and community inclusion, including: "eligibility", "design and implementation", and "evaluation" of community access services. Discourse analysis highlighted inequity inherent in the language used in the documents studied, which continues to define and treat people with disabilities as a homogenous group to be managed separately. Findings from this study will contribute to strengthening community inclusion of people with disabilities by focusing on the inclusion of their voices in policies related to community participation and community access within Australia.